Tradisi Sedekah Bumi sebagai Ekspresi Rasa Syukur dalam Budaya Keagamaan Warga Nahdlatul Ulama Desa Tegowanu Wetan, Kec. Tegowanu, Kabupaten Grobogan - Umi Nur Amiroh (Lakpesdam PCNU Kota Salatiga, 2024)
The Sedekah Bumi (Merti Bumi/Apitan) tradition is a socio-religious practice of agrarian communities that has been transmitted across generations and continues to be preserved in Tegowanu Wetan Village. This tradition is not only understood as an annual post-harvest celebration, but also as a medium for collective gratitude to God and, at the same time, respect for the village’s founding ancestors. Against this backdrop, the study formulates three research questions: (1) how the Sedekah Bumi tradition is carried out in Tegowanu Wetan Village as a social practice that is inherited and institutionalized within the community; (2) what Sedekah Bumi means for Nahdliyin residents as an agrarian tradition that embodies religious gratitude as well as historico-cultural reverence; and (3) what values and functions it contains (sociological, theological, and ecological), along with their implications for the community’s socio-religious life. This study employs a qualitative method with an empirical approach through field research, using observation and interviews as data collection techniques, supported by a literature review. The findings show that Sedekah Bumi is held regularly once a year in the month of Apit (Javanese calendar) through a series of rituals: communal cooking, Islamic sermon and collective prayers (pengajian), communal feast (selametan), cleansing of village heirlooms, and a wayang kulit (shadow puppet) performance. The tradition is interpreted as an expression of gratitude for the harvest, an effort to “safeguard/bless the village,” and an act of honoring ancestors, thereby integrating religious and local cultural dimensions within the lived religiosity of Nahdliyin residents. Prominent values include sociological values (cohesion and solidarity), theological values (strengthening gratitude through collective prayer), and ecological values (awareness of preserving heritage and the environment), accompanied by pragmatic-economic functions such as entertainment and temporary economic activities that further reinforce the tradition’s continuity